14 Stat. 176 (1866) - (:unkn) unknown (My University, 1868)
§ 14: Reaffirmed that freedmen were entitled to "full and equal benefit of all laws and proceedings concerning personal liberty [and] personal security . . . including the constitutional right to keep and bear arms."
Keywords: GUARANTEED RIGHT